PENYUSUTAN ARSIP MENCIPTAKAN PRODUKTIVITAS KERJA PEGAWAI - Lilis Ina Rismawati (Politeknik Negeri Semarang, 2014)
Archives as the result of this administration continue to grow in akumulatif, as a result of getting more complex functions and tuggs, then an archive as a source of information, need proper management as an effort to increase effectiveness, efficiency of labor productivity employees so that by contrivances orderly whoose archive make it easier for employees in implementing administrative offices.Increase in the number of archives are potential to cause problems among others : storage space to be full, extravagance change for the use of equipment, the provision of energy and its treatment. Therefore necessary depreciation archive in institutions with the way : depreciation retention that has outlived archive and having no value, transfer the files of the inaktif of processing unit into unit chancery, the static archive of chancery to archive institution.